PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP ANAK YANG MENJADI KORBAN TINDAK PIDANA DI WILAYAH HUKUM PENGADILAN NEGERI BANYUMAS - Dwiatmodjo, Haryanto (Jurnal Dinamika Hukum, 2011)
Forms of legal protection of children as victims of crime in the jurisdiction of the District Court of Banyumas on the level of investigation in the Police with given rehabilitation. At the level Prosecutor's just no real form of protection for victim.  Who's in Court level there are two forms of protection, the first form of protection of identity in the mass media coverage to avoid labeling, and second with the provision of safety guarantees. Realization of the protection of children who are victims of crime has not been up to since the rights of victims, get rehabilitation, compensation, and restitution difficult to manage their funds because there is confusion of the law enforcement agency where the source of funds to be allocated. Barriers to the very fundamentals of the implementation of child protection as a victim was the absence of implementation costs to maximize protection. Keywords: Legal protection, children, victims